Analysis of the Effectiveness of Patient Flow Management in Improving Service Speed - Hermawan, Randy; Umi Narinawati; Bobi Kurniawan (Jurnal Locus Penelitian dan Pengabdian, 2026)
Speed of service is a vital indicator of the quality of health services, but the imbalance between surge in patient visits and facility capacity often leads to bottlenecks and long wait times. This study aims to analyze the effectiveness of the implementation of Patient Flow Management in improving service speed and operational efficiency in health facilities. The study used a quantitative descriptive approach through field observation (time and motion study), operational data measurement, and satisfaction survey at a private hospital during the period from July to September 2025. The results showed a significant impact post-implementation, where the average total waiting time was reduced by 41.5%, the doctor's workload ratio became more balanced from 1:38 to 1:26, and there was an increase in patient satisfaction scores by 30%. This efficiency is achieved through an effective strategy of digitizing the queue system and redistributing triage loads. In conclusion, Patient Flow Management has proven to be effective as an operational solution to unravel service density, but its success relies heavily on the integration of information systems and management support in adapting staff work cultures.